Validity of Mycobacterium tuberculosis Antigens Cocktail: ESAT-6, CFP-10 and MPT64 in Sputum and Cerebrospinal Fluid for Pulmonary Tuberculosis and Tuberculous Meningitis Diagnosis - Dewi Kartika Turbawaty; Nenny Gustiani; Livia Noviani; Ida Parwati (International Journal of Integrated Health Sciences, 2015)
Objective: Rapid and accurate TB diagnostics play an important role in detecting the disease. Currently, antigens secreted (ESAT-6, CFP-10 and MPT64) by M. tuberculosis and encoded by genes “Region of Difference” (RD)1, RD2 and RD3 give an opportunity for rapid TB diagnosis. Genomic region RD1-RD3 was deleted in M. bovis BCG strains and absent in mycobacteria other than M. tuberculosis. This property is advantageous because it enable to create a specific diagnostic tools for M. tuberculosis infection. The aim of this study is to determine the validity of TB antigens cocktail (ESAT-6, CFP-10 and MPT64) for pulmonary tuberculosis and TB meningitis diagnosis. Methods: This is a descriptive observational study design. The study was conducted at the Clinical Pathology Laboratory of Dr. Hasan Sadikin General Hospital during September 2012 until March 2013 for the pulmonary tuberculosis study and from January 2014 to May 2014 for the TB meningitis study. The TB antigen cocktail rapid immunochromatography (ICT) test was done on all of the samples. The sputum and CSF were cultured as gold standards. Results: There were 149 pulmonary and 41 TB meningitis subjects. The sensitivity of TB antigens cocktail rapid ICT for diagnosing pulmonary tuberculosis was 95.7% with a speciﬁcity of 87.2%. Of 41 TB meningitis subjects, based on Marais criteria, there were 6 (16%) subjects with a definite TB meningitis, 26 (63%) subjects with probable TB meningitis and 9 (21%) subjects with possible TB meningitis. The sensitivity and specificity of TB antigens cocktail rapid ICT for TB meningitis diagnosis were 83.3% and 68.5% respectively. Conclusions: In this study, rapid ICT TB antigens cocktail (ESAT-6, CFP-10 and MPT64) from sputum sample has good validity for diagnosing a pulmonary tuberculosis, and from CSF sample has moderate validity to diagnose TB meningitis. Keywords: M. tuberculosis culture, pulmonary TB, TB meningitis, TB antigens cocktail (ESAT-6, CFP-10 and MPT64) rapid ICT DOI: 10.15850/ijihs.v3n2.585